2010
DOI: 10.4103/0972-124x.76928
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oral hygiene and periodontal status in patients with clefts of palate and patients with unilateral cleft lip, palate and alveolus

Abstract: Aim:This study was conducted to analyze and compare the oral hygiene and periodontal status in patients with clefts of palate (CP) and patients with unilateral cleft lip, palate and alveolus (UCLPA).Materials and Methods:The study group consisted of 120 cleft patients. Subjects were divided into two groups of 60 each. Group I - patients with UCLPA and Group II - patients with CP. For comparison, all the four quadrants were defined, Q1-right upper quadrant, Q2-left upper quadrant, Q3-left lower quadrant and Q4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 15 publications
0
28
0
8
Order By: Relevance
“…10 Researchers comparing sites from teeth adjacent to an alveolar cleft with unaffected control sites found that the radiographic alveolar bone level was significantly more apical at the cleft region, whereas the probing attachment level was similar in the cleft and control regions. 9,11,12 These findings suggested the presence of a long connective tissue attachment in the cleft regions. 12 The results of these studies are consistent with the report of Quirynen et al 2 that teeth in the cleft had significantly more bone loss compared with contralateral noncleft control teeth.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…10 Researchers comparing sites from teeth adjacent to an alveolar cleft with unaffected control sites found that the radiographic alveolar bone level was significantly more apical at the cleft region, whereas the probing attachment level was similar in the cleft and control regions. 9,11,12 These findings suggested the presence of a long connective tissue attachment in the cleft regions. 12 The results of these studies are consistent with the report of Quirynen et al 2 that teeth in the cleft had significantly more bone loss compared with contralateral noncleft control teeth.…”
Section: Introductionmentioning
confidence: 69%
“…7,8 The few studies that have analyzed the periodontal status of these persons showed a high incidence of plaque and bleeding on probing and a high level of periodontal attachment loss. 8,9 In osseous clefts, the osseous structures are absent or poorly developed in the region of periodontal supportive tissues. 9 Some reports suggest that the cleft area affects the periodontal tissues of the teeth in close proximity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations